To study association of Neutrophil- Lymphocyte ratio with vascular complications in Type-2 Diabetes - Gowda, Shilpa Tumkur Andane; Kusumakar, Shahari Hegde; Ramamurthy, Raveendra Kodur; Govindaiah, Rohith Maraludevanapura (Asian Journal of Medical Sciences, 2021)
Background: Diabetes is a pro-thrombotic state associated with increased risk of atherosclerosis and inflammation. Neutrophil lymphocyte ratio (NLR) provides information about early and subclinical inflammation and thus may act as a prognostic marker for vascular complications in type 2 diabetes. Aims and Objective: To analyze the correlation between Neutrophil- Lymphocyte ratio in diabetics with and without vascular complications. Materials and Methods: A total of 111 patients admitted in Victoria hospital and Bowring & Lady Curzon hospital attached to Bangalore Medical College and Research Institute from NOV 2018 to MAY 2020 were studied. The data was collected according to the proforma in terms of history, clinical examination and the necessary investigations. NLR was observed in type 2 diabetic patients and was compared in those with complications and without complications. Results: The NLR was higher in diabetics with vascular complications compared to those without complications, 2.8 ± 0.7 fl versus 6.8 ± 3.1 fl (P< 0.001), respectively. In this study, Mean N (%), In No Vascular Complications was 61.7 ± 10.6 and with vascular complications was 79.9 ± 9.5. Mean L (%) in No Vascular Complications was 23.7 ± 5.8. Mean N (%), In No Vascular Complications was 61.7 ± 10.6 and with vascular complications was 79.9 ± 9.5. There was a significant difference in mean N (%) mean L (%) and NLR in comparison with respect to Complications. Conclusion: This study showed significantly higher NLR in diabetic patients with vascular complications. Hence, NLR can be used as a simple parameter to assess the vascular complications in diabetes.